2019
DOI: 10.1177/1071100719847700
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Early Radiographic Outcomes of Triplanar Tarsometatarsal Arthrodesis With Early Weightbearing

Abstract: Background:Hallux valgus is a multiplanar deformity of the first ray. Traditional correction methods prioritize the transverse plane, a potential factor resulting in high recurrence rates. Triplanar first tarsometatarsal (TMT) arthrodesis uses a multiplanar approach to correct hallux valgus in all 3 anatomical planes at the apex of the deformity. The purpose of this study was to investigate early radiographic outcomes and complications of triplanar first TMT arthrodesis with early weightbearing.Methods:Radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
0
14
1
Order By: Relevance
“…Several recent studies have demonstrated low nonunion rates and maintained correction after a first TMT arthrodesis, even with early weightbearing. 1,5,6,8,9 It is important to mobilize patients early after surgery to avoid the complications of prolonged immobilization. The results of our study showed that significant reductions in bony and soft tissue foot widths may still be achieved after a triplanar first TMT arthrodesis with early weightbearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated low nonunion rates and maintained correction after a first TMT arthrodesis, even with early weightbearing. 1,5,6,8,9 It is important to mobilize patients early after surgery to avoid the complications of prolonged immobilization. The results of our study showed that significant reductions in bony and soft tissue foot widths may still be achieved after a triplanar first TMT arthrodesis with early weightbearing.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed operative technique has been previously published. 9 In summary, a dorsal longitudinal incision was centered over the first TMT joint. The first TMT joint was exposed dorsally and medially via subperiosteal dissection, followed by a plantar release of the joint.…”
Section: Methodsmentioning
confidence: 99%
“…The operative procedure has been described earlier in detail (Supplemental Video). 31,36,39,40 Although severity-based algorithms would advocate distal metatarsal procedures for lower IMAs, it was the authors’ preference to address the deformity from an anatomic basis at the center of rotation and angulation. 18 The main principle of the technique was a “correct then cut” method using a precision standardized cutting guide that allowed for minimal bone resection of joint surfaces while aligning the first ray in 3 dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Although the concept of 3-dimensional deformity correction is novel and exciting in hallux valgus surgery, it is not unique to Lapiplasty and longer-term studies are needed to critically evaluate clinical outcomes. 9,11…”
Section: Pertinence To Foot and Ankle Surgerymentioning
confidence: 99%